Pengaruh Faktor Risiko Terhadap Initial return IPO Pada Perusahaan Yang Melakukan IPO - Mulyadi, Sebastian Taniel; Lukman, Hendro; Simina, Juni (Jurnal Paradigma Akuntansi, 2025)
This study attempts to assess whether internal risk, external risk, investment risk, and business risk have an impact on the first return of IPOs conducted on the Indonesia Stock Exchange between 2020 and 2021. This study used a form of purposive sampling to collect data from as many as 90 companies. Version 21 of the SPSS (Statistical Product and Service Solutions) software was used to process the data. Internal risk, external risk, and investment risk were all negative and did not have a substantial impact on the first return of an IPO, according to the results of a multiple linear regression analysis of the data. While business risk is positive and has no major effect on the IPO's initial return, business risk is positive and has no effect. The implication of this research is that every firm planning an IPO or going public must present comprehensive and precise information and underline the risk factors that investors must consider.